Dissection of Allelic Variation Underlying Floral and Fruit Traits in Flare Tree Peony (Paeonia rockii) Using Association Mapping - Guo, Xin; He, Chunyan; Cheng, Fangyun; Zhong, Yuan; Cheng, Xinyun; Tao, Xiwen (Frontiers in Genetics, 2021)
Allelic variation in floral quantitative traits including the elements of flowers and fruits is caused by extremely complex regulatory processes. In the genetic improvement of flare tree peony (Paeonia rockii), a unique ornamental and edible oil woody species in the genus Paeonia, a better understanding of the genetic composition of these complex traits related to flowers and fruits is needed. Therefore, we investigated the genetic diversity and population structure of 160 P. rockii accessions and conducted single-marker association analysis for 19 quantitative flower and fruit traits using 81 EST-SSR markers. The results showed that the population had a high phenotypic diversity (coefficients of variation, 11.87% to 110.64%) and a high level of genetic diversity (mean number of alleles, NA = 6.09). These accessions were divided into 3 subgroups by STRUCTURE analysis and a neighbour-joining tree. Furthermore, we also found a low level of linkage disequilibrium between these EST-SSRs and, by single marker association analysis, identified 134 significant associations, including 4 flower traits with 11 EST-SSRs and 10 fruit traits with 32 EST-SSRs. Finally, based on the sequence alignment of the associated markers, P280, PS2, PS12, PS27, PS118, PS131,and PS145 may be considered potential loci to increase the yield of flare tree peony. These results laid the foundation for further analysis of the genetic structure of some key traits in P. rockii, and had an obvious potential application value in marker-assisted selection breeding.